Psychological Analysis of Elsa’s Character in Novel “My Grandmother Asked Me to Tell You She’s Sorry” by Fredrik Backman - Gultom, Yessy Frietama; Retnomurti, Ayu Bandu; Kurniawaty, Julia Bea (Foremost Journal, 2024)
The objectives of this study are to describe the psychological aspects of the character's story and identify the many forms of psychology exhibited by the main character in the novel "My Grandmother Asked Me to Tell You She's Sorry" authored by Fredrik Backman. The research methodology employed is descriptive qualitative. The present study employs the theoretical framework proposed by Soto and John (2017, p. 8). The research findings indicate that the traits of Openness account for 5 (25% of the total) and are exemplified by Elsa's covert departure from her apartment to accompany her grandmother. Similarly, the traits of Conscientiousness also contribute to 5 (25% of the total), exemplified by Elsa's unwavering determination to complete the task assigned by her grandmother. Lastly, the traits of Neuroticism account for 5 (25% of the total) and are evidenced by Elsa feeling pressured by bullying from some of her classmates when she holds a different opinion from one of them. Data findings indicate that Agreeableness is characteristic of 3 (15%) of the participants. For instance, Elsa demonstrates conflict and disagreement with her mother after being summoned by the Principal for attacking one of her friends. On the other hand, Extraversion is characteristic of 2 (10%) of the participants. For instance, Elsa isolates herself from having many friends at school and prefers to confide in her grandmother.